Strategi Promosi Rumah Makan Soponyono Dalam Mempertahankan Pelanggan Di Kecamatan Kesu’ Kabupaten Toraja Utara - Jeanne Fransisca Bokko; Abedneigo.C. Rambulangi; Mey.E. Limbongan (Universitas Kristen Indonesia Toraja, 2023)
This research aims to answer the questions (1) How is the promotion and promotion strategy carried out by Rumah Makan Soponyono? (2) How to retain customers? This study used descriptive qualitative method. Data was collected by means of observation, interviews and documentation with business owners, employees and customers of Soponyono Restaurant. The results obtained from this research are the Promotion Strategy for Soponyono Restaurant using promotional media using social media, namely WhatsApp and how to retain customers by exchanging good, polite and friendly messages towards customers and convincing customers that at Soponyono Restaurant the food and drink menus are delicious. , delicious and comfortable place.